Kształcenie ponadgimnazjalne/ponadpodstawowe uczniów ze specjalnymi potrzebami edukacyjnymi – pomiędzy edukacją ogólnokształcącą a zawodową – na przykładzie miasta Łodzi - Jachimczak, Beata (Studia Edukacyjne, 2018)
The purpose of this article is to analyze the post-gymnasium/ post-primary education in the context of students’ special needs. In the first part of the article, the author presents the problem of shaping educational paths of students with special educational needs. Then the author briefly describes the changes in the education in mainstream secondary schools and vocational secondary schools (including basic vocational schools) during the transformation period. In the further part of this article, the author analyzes the educational opportunities and limitations of students with special educational needs in their individual and environmental predispositions and with reference to the results of external examinations. The article ends with the indication of the need to support students with special educational needs in shaping their educational and professional choices.